Proteomics Reveals an Increase in the Abundance of Glycolytic and Ethanolic Fermentation Enzymes in Developing Sugarcane Culms During Sucrose Accumulation - Boaretto, Luis Felipe; Labate, Mônica Teresa Veneziano; Franceschini, Livia Maria; Cataldi, Thais Regiani; Budzinski, Ilara Gabriela F.; Moraes, Fabricio Edgar de; Labate, Carlos Alberto (Frontiers in Plant Science, 2021)
Sugarcane is an economically important crop contributing to the world’s sugar and ethanol production with 80% and 40%, respectively. Despite of its importance as the main crop for sugar production, the mechanisms involved in the regulation of sucrose accumulation in sugarcane culms are still poorly understood. The aim of this work was to compare the quantitative changes of proteins in juvenile and maturing internodes at three stages of plant development. Label free shotgun proteomics was used for protein profiling and quantification in internodes 5 (I5) and 9 (I9) of 4, 7 and 10 month-old-plants (4M, 7M and 10M, respectively). The I9/I5 ratio was used to assess the differences in abundance of common proteins at each stage of internode development. I9 of 4M plants showed statistically significant increases in the abundance of several enzymes of the glycolytic pathway and proteoforms of alcohol dehydrogenase (ADH) and pyruvate decarboxylase (PDC). These changes in enzymes content were followed by major increases of proteins related to O2 transport like hemoglobin 2, ROS scavenging enzymes, and enzymes involved in the Ascorbate/Glutatione system. Besides, intermediates from tricarboxylic acid cycle (TCA) were reduced in I9-4M, indicating that the increase in abundance of several enzymes involved in glycolysis, pentose phosphate cycle and TCA, might be responsible for higher metabolic flux, reducing its metabolites contents. The results observed in I9-4M indicate that hypoxia might be the main cause of the increased flux of glycolysis and ethanolic fermentation to supply ATP and reducing power for plant growth, mitigating the reduction in mitochondrial respiration, due to the low oxygen availability inside the culm. As the plant matured and sucrose accumulated to high levels in the culms, the proteins involved in glycolysis, ethanolic fermentation and primary carbon metabolism were significantly reduced.